Association between a polygenic and family risk score on the prevalence and incidence of myocardial infarction in the KORA-F3 study. (July 2022) - Schnitzer, Florian; Forer, Lukas; Schönherr, Sebastian; Gieger, Christian; Grallert, Harald; Kronenberg, Florian; Peters, Annette; Lamina, Claudia
Abstract: Background and aims: Genetic risk scores for common diseases as myocardial infarction (MI) gain increasing attention for individual's risk prediction. One might wonder if assessing family history becomes redundant. It was the aim of this study to evaluate the amount of shared information between family history and genetic risk scores and to assess their independent and combined effects on prevalent and incident MI risk. Methods: A genome wide polygenic risk score (PGS) and one family risk score (FamRS) were calculated in a population-based study from Southern Germany (n = 3071) with up to 11 years of follow-up. Logistic and Cox Regression models were used adjusting for lifestyle and classical risk factors. Results: A right shift in MI risk for increasing values of PGS was found, with. considerably increasing ORs along the top quantiles of PGS (OR = 3.03 for top 10%; OR = 5.55 for top 2.5%). The PGS was not associated with incident MI cases, though. The FamRS was significantly associated with both prevalent and incident MI cases with an OR of 2.9 for participants with a strong positive family history compared to average. ORs and HRs did hardly change in a combined model including both measures, indicating independent contribution to MI risk. The simultaneous addition of PGS and FamRS to a model including classical risk factors significantly enhanced prediction for prevalent cases and non-cases ( p = 3.28 × 10 −5 ). Conclusions: These findings emphasize that both genetic information and family history are relevant for the determination of MI risk and that neither of them can replace the other. Graphical abstract: Image 1 Highlights: A genome-wide polygenic risk score (PGS) was shown to be a strong risk predictor for especially "early" prevalent myocardial infarction (MI) cases. A family risk score (FamRS) was a stronger predictor than simpler family history measures as "diseased parents". The FamRS was highly informative for both prevalence and incidence. Addition of PGS and FamRS to a model including classical risk factors enhanced prediction for prevalent cases and non-cases.